Refining in-vivo models of pulmonary fibrosis - Habgood, Anthony (2018)
Idiopathic pulmonary fibrosis (IPF) is a progressive disease with limited treatment options. IPF is characterized by excessive collagen deposition within the lung resulting in loss of lung function and a survival rate worse than most cancers. There is an urgent need to develop and better characterise animal models of this disease to further our understanding of its pathophysiology and to assist in the development of new pharmacological treatments. Researching respiratory diseases and the development of new therapies relies on the use of robust in vivo models.